E-learning and Digital Training in Healthcare Education Current Trends and New Challenges - Proença, Luís; Mendes, José João; Botelho, João; Machado, Vanessa (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is dedicated to the current trends and new challenges that have emerged from the new e-learning environment, focusing on its potential to revolutionize Healthcare Education and exploring how it may help to better prepare future healthcare professionals for their daily practice. "E-learning and Digital Training in Healthcare Education: Current Trends and New Challenges" contains several research articles focused on new insights into the use of interactive and intuitive e-learning tools and innovative teaching methodologies that engage healthcare students in the new web-based environment training. It also includes several case studies of 'pathfinder' e-learning initiatives and surveys related to the penetration and acceptance of digital training in Healthcare Education.